Alterações comportamentais, estruturais e níveis de fatores neurotróficos e citocinas em modelo experimental de parkinsonismo: efeitos do exercício físico - Roseane Marques Ribeiro (2013)
The ageing of global population and the increase inincidence and prevalence of neurodegenerative diseases such as Parkinson's disease, highlight the importance of studies that aim to understand the underlying mechanisms of this disease. In e Parkinson´s disease there is dopaminergic neurons death especially in the substantia nigra midbrain generating motors and no motors symptoms. In this study we investigated whether previous aerobic training on atreadmill for 30 consecutive days at a moderate intensity and individualized speed could have neuroprotective effects in male Holtzman rats under an MPTP experimental model through intranasal infusion, neurotoxin specific to those neurons. Theresults show that physical exercise could improve physical fitness observed byincreased speed and distance travelled. Besides, treadmill exercise was able to raise open field exploratory activity evidenced by increase in number of quadrants crossed, speed average, rearing number and duration. We also observed increased BDNF levels in the ventral midbrain, and decreases TNF-and IL-10 levels in striatum. Furthermore, the lesion induced by MPTP decreases open field exploratory curiosity, reducing the number of quadrants crossed, maximum speed, active time, rearings number and duration, number of grooming, and increases the freezing timefrom 21 days post-infusion on. MPTP generates structural changes such as death of dopaminergic neurons, astrocytes and gliovascular unit alterations in theventral midbrain, as well as striatal BDNF elevation, GDNF and TNF -decreasing in ventral midbrain. The animals subjected to aerobic exercise showed no locomotor deficits, but an increase of exploratory curiosity 31 days post-infusion. Thus, we think that intranasal infusion of MPTP produces behavioral, structural and biochemical changes in nigrostriatal system and aerobic exercise treadmill can prevent /attenuate the development of parkinsonism.